2020
DOI: 10.21307/jofnem-2020-083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed-applied fluopyram on Meloidogyne incognita infection and maturity in cotton and soybean

Abstract: Fluopyram is being used to manage plant-parasitic nematodes in cotton (Gossypium hirsutum) and soybean (Glycine max), but the duration and depth of root protection from Meloidogyne incognita by seed-applied fluopyram is unknown. Both M. incognita susceptible cotton, Stoneville 'ST 4848 GLT', and soybean, Delta Grow 'DG 4880 GLY', cultivars were treated with fluopyram or abamectin and inoculated with second-stage juveniles in two greenhouse studies. Root penetration by M. incognita was suppressed from 7 to 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…even when used in low doses below what is advised, whether in the field or greenhouse, and reduces nematode density. (Faske and Hurd, 2015;Dahlin et al, 2019;Hawk, 2019). In line with earlier research (Di Sanzo, 1973;Akter et al, 2021), the results of the Furadan treatment likewise shown a reduction in the number of knots compared to the inoculum treatment.…”
Section: Field Experiencesupporting
confidence: 87%
“…even when used in low doses below what is advised, whether in the field or greenhouse, and reduces nematode density. (Faske and Hurd, 2015;Dahlin et al, 2019;Hawk, 2019). In line with earlier research (Di Sanzo, 1973;Akter et al, 2021), the results of the Furadan treatment likewise shown a reduction in the number of knots compared to the inoculum treatment.…”
Section: Field Experiencesupporting
confidence: 87%
“… Hawk and Faske (2020) indicated that cotton and soybean seeds treatment with abamectin and fluopyram suppressed M. incognita root penetration that contributes to forming root galls and nematode reproduction in cotton and soybean plants, and suggested that these nematicides at low concentration can inhibit nematode motility for penetrating the roots.…”
Section: Discussionmentioning
confidence: 99%
“…At concentrations greater than 50 mg/L hatching inhibition is achieved without recovery [115]. In greenhouse and field trials on tomatoes, carrots, cotton (Gossypium hirsutum), potato, and soybean, fluopyram has been effective at managing PPNs [116][117][118].…”
Section: Marketed As An Active Ingredient Inmentioning
confidence: 99%